Análisis de riesgo en la infraestructura de tecnologías de información en la Cooperativa de Ahorro y Crédito Calceta Limitada - Dávila Muñoz, Mayra Alexandra (2015)
The research aimed to develop a risk analysis to determine the degree of exposure of undesirable events in the information technology infrastructure of the Credit and Saving Union Calceta Limited in Bolivar Canton, Magerit methodology was used to develop this type of work specifically, threats and risks where identified to which the Bank are exposed and the impact would be materialized, this was done to prioritize the most important tasks in the organization, safeguards where proposed for the infrastructure of Information Technology in the institution, to know how and when to act against risks, which helps the institution to understand their vulnerabilities and take necessary measures for the safety of the assets and not compromise the integrity, confidentiality and availability of data.